Supply chain strategy, flexibility and performance in the Gauteng fast-moving consumer goods (FMCG) industry - Ngomane, Sikhulile Rhine (Vaal University of Technology, 2023)
The successful implementation of supply chain strategy has received significant attention among literature and practitioners, due to its importance in contributing to company success. The success of the FMCG industry in South Africa has also been attributed to the effectiveness of its supply chain strategies. However, the industry faces numerous challenges such as miscellaneous risks that include the potential loss of key suppliers, innovation, and risk, planning and forecasting, power outages in manufacturing plants and the fact that only a limited amount of safety stock can be held to offset uncertainty. It also faces difficulties in improving supply and demand, which further extends to transforming supplier relationships into effective collaboration. Thus, this study applies supply chain strategy to the FMCG industry in South Africa, and seeks to establish the connection between supply chain strategies, flexibility (SCF) and performance (SCP) in the sector. The methodological procedure in this study was guided by the positivist paradigm which is embedded in quantitative and causal designs. A sample of 228 respondents purposively drawn from the FMCG industry in Gauteng province participated in the survey. The collected data were tested using descriptive and inferential statistics. The specific statistical techniques applied included the analysis of frequency distributions, percentages, mean scores, exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and hypotheses tests using partial least squares-based structural equation modelling. The empirical results showed that two supply chain strategies, namely, organisational learning and supplier integration contribute significantly to SCF. In turn, SCF contributes positively to financial and non-financial performance. Supply chain strategies such as innovation, risk management and customer orientation were statistically insignificant in predicting SCP. The study is significant because it identifies that supply chain strategies are important in developing flexible FMCG supply chains in South Africa. It also confirms the importance of SCF in improving the performance of FMCG supply chains. The study may therefore be used as a reference source for information on the improvement of SCP in FMCG supply chains.
M. Tech. (Department of Logistics Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Supply chain strategy; Supply chain flexibility; Supply chain performance; FMCG industry; Gauteng province; Dissertations, Academic -- South Africa.; Business logistics.